2019
DOI: 10.1590/1516-3180.2018.0431140319
|View full text |Cite
|
Sign up to set email alerts
|

The CHA2DS2-VASc score for predicting atrial fibrillation in patients presenting with ST elevation myocardial infarction: prospective observational study

Abstract: BACKGROUND: Atrial fibrillation (AF) is the most common form of supraventricular arrhythmia following ST-elevation myocardial infarction (STEMI). The CHA 2 DS 2-VASc and CHADS 2 scores are used to estimate thromboembolic risk in cases of AF. Their usefulness in predicting the development of AF in patients presenting STEMI is unknown. OBJECTIVE: To evaluate the predictive value of the CHADS 2 and CHA 2 DS 2-VASc scores in patients with AF following STEMI. DESIGN AND SETTING: This prospective cohort study on 696… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
17
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 28 publications
3
17
2
3
Order By: Relevance
“…11 In recent years, several studies have suggested that CHADS2, R2CHADS2, and CHA2DS2-VASc could predict new occurrence of AF in the general population, [12][13][14][15] patients after AF ablation, 16 or patients with acute coronary syndrome. 17,18 In addition, the individual components in these scores are also the potential risk factors of AF in HF patients. Therefore, it would be interesting to determine if the CHADS2, R2CHADS2, and CHA2DS2-VASc scores could predict AF in HFpEF patients.…”
Section: Introductionmentioning
confidence: 99%
“…11 In recent years, several studies have suggested that CHADS2, R2CHADS2, and CHA2DS2-VASc could predict new occurrence of AF in the general population, [12][13][14][15] patients after AF ablation, 16 or patients with acute coronary syndrome. 17,18 In addition, the individual components in these scores are also the potential risk factors of AF in HF patients. Therefore, it would be interesting to determine if the CHADS2, R2CHADS2, and CHA2DS2-VASc scores could predict AF in HFpEF patients.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has shown an association between CHA2DS2-VASc risk score and reperfusion failure after thrombolytic therapy in patients with STEMI 7 . Moreover, we showed that CHA2DS2-VASC score have been predicted AF following STEMI and associated with epicardial fat tissue 8,9 .…”
Section: Introductionmentioning
confidence: 72%
“…The application of this scoring system for the prediction of thromboembolic events is not restricted to patients with AF; it can also be applied to patients without AF such as those with heart failure [2] or chronic obstructive pulmonary disease [3] and those after coronary artery bypass grafting (CABG) [4,5]. It can also predict the occurrence of AF in varieties of conditions such as diabetes [6], systemic lupus erythematosus [7], myocardial infarction [8], and cardiac surgeries including CABG [9][10][11]. In addition, the CHA 2 DS 2 -VASc score plays a role in the prediction of events other than stroke and AF such as failed reperfusion after thrombolytic therapy [12], the no-reflow phenomenon [13], and contrast-induced nephropathy [14].…”
Section: Introductionmentioning
confidence: 99%